2022
DOI: 10.1002/acn3.51574
|View full text |Cite
|
Sign up to set email alerts
|

A double‐blind, randomized, placebo‐controlled phase 2 trial evaluating the selective dihydroorotate dehydrogenase inhibitor vidofludimus calcium in relapsing‐remitting multiple sclerosis

Abstract: Objective Inhibition of dihydroorotate dehydrogenase suppresses magnetic resonance imaging brain lesions and disease activity in multiple sclerosis but has limiting tolerability. We assessed the safety and efficacy of vidofludimus calcium, a novel, selective dihydroorotate dehydrogenase inhibitor, in patients with relapsing‐remitting multiple sclerosis. Methods This double‐blind, 24 weeks, placebo‐controlled, phase 2 trial (EMPhASIS) enrolled patients 18–55 years with relapsing‐remitting multiple sclerosis. El… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…5A and B ). Notably, the peak plasma concentration (C max ) of vidofludimus calcium used in relapsing-remitting multiple sclerosis is 8.738–14.571 ​μmol/L ( Muehler et al., 2020a ; Fox et al., 2022 ). And the C max of vidofludimus calcium used to combat SARS-CoV-2 infection in patients hospitalized with COVID-19 is 14.323–14.57 ​μmol/L ( Vehreschild et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…5A and B ). Notably, the peak plasma concentration (C max ) of vidofludimus calcium used in relapsing-remitting multiple sclerosis is 8.738–14.571 ​μmol/L ( Muehler et al., 2020a ; Fox et al., 2022 ). And the C max of vidofludimus calcium used to combat SARS-CoV-2 infection in patients hospitalized with COVID-19 is 14.323–14.57 ​μmol/L ( Vehreschild et al., 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…They are structurally distinct from leflunomide and teriflunomide and exhibit favorable safety profiles ( Jones et al., 2021 ). Vidofludimus calcium has been well-studied in over 1400 healthy volunteers or patients with immune-related conditions with a safety and tolerability profile similar to placebo ( Muehler et al., 2020a ; Fox et al., 2022 ). Vidofludimus calcium has advanced in phase 3 clinical development for patients with multiple sclerosis ( Therapeutics ) or hospitalized with COVID-19 ( ClinicalTrials.gov NCT04379271).…”
Section: Discussionmentioning
confidence: 99%
“…Hypertriglyceridemia occurred more frequently in the patients treated with vidofludimus calcium compared to placebo although the reason for this observation is not clear. Hypertriglyceridemia has not been associated with DHODH inhibitors, including vidofludimus calcium, so the apparent higher incidence of hypertriglyceridemia in patients treated with vidofludimus calcium is unlikely to be related to inhibition of DHODH [ 27 , 29 32 ]. All non-published clinical studies investigating vidofludimus calcium also have no reported adverse events of hypertriglyceridemia.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, non-invasive intravesical therapy can preserve high local concentrations of drugs by direct exposure. Recent studies revealed the anti-inflammatory and immunomodulatory effects of selective dihydroorotate dehydrogenase inhibitors (DHODHi) via suppressing mitochondrial pyrimidine synthesis, exemplified by clinically investigational vidofludimus (IMU-838) 7 . While elevated levels of interleukin (IL)-17A are found in the bladder tissues and urine of IC patients, IL-17A triggers the release of other pro-inflammatory cytokines 8 .…”
Section: Introductionmentioning
confidence: 99%